LIVER TRANSPLANTATION AND HBV INFECTION - O. I. Andreytseva; A. V. Kozlova; V. E. Sutkin (Вестник трансплантологии и искусственных органов, 2009)
The paper describes the modern approaches in treatment of hepatitis B virus (HBV)-infected patients who underwent liver transplantation. The patients with HBV liver cirrhosis and waiting for orthotopic liver transplantation (OLT) have to receive long-term therapy with nucleos(t)ide analogs right up to liver transplantation. The paper discuss the different schemes of prophylaxis of recurrent HBV infection during post-transplantation and specific treatment of HBV infection after liver transplantation as well as possibilities of orthotopic liver transplantation for patients with liver cancer.